Plicosepalus acacia Extract and Its Major Constituents, Methyl Gallate and Quercetin, Potentiate Therapeutic Angiogenesis in Diabetic Hind Limb Ischemia: HPTLC Quantification and LC-MS/MS Metabolic Profiling - Asmaa R. Abdel-Hamed; Eman T. Mehanna; Reem M. Hazem; Jihan M. Badr; Dina M. Abo-Elmatty; Maged S. Abdel-Kader; Marwa S. Goda (MDPI AG, 2021)
Plicosepalus acacia (Fam. Loranthaceae) has been reported to possess hypoglycemic, antioxidant, antimicrobial, and anti-inflammatory effects. Liquid chromatography combined with tandem mass spectrometry (LC-MS/MS) analysis revealed the presence of a high content of polyphenolic compounds that are attributed to the therapeutic effects of the crude extract. In addition, methyl gallate and quercetin were detected as major phytomedicinal agents at concentrations of 1.7% and 0.062 g%, respectively, using high-performance thin layer chromatography (HPTLC). The present study investigated the effect of the P. acacia extract and its isolated compounds, methyl gallate and quercetin, on hind limb ischemia induced in type 1 diabetic rats. Histopathological examination revealed that treatment with P. acacia extract, methyl gallate, and quercetin decreased degenerative changes and inflammation in the ischemic muscle. Further biochemical assessment of the hind limb tissue showed decreased oxidative stress, increased levels of nitric oxide and endothelial nitric oxide synthase (eNOS), and enhancement of the levels of heme oxygenase-1 (HO-1) and vascular endothelial growth factor (VEGF) in the groups treated with methyl gallate and quercetin. Expression levels of hypoxia inducible factor-1 alpha (HIF-1α), VEGF, fibroblast growth factor-2 (FGF-2), and miR-146a were upregulated in the muscle tissue of methyl gallate- and quercetin-treated groups along with downregulation of nuclear factor kappa B (NF-κB). In conclusion, P. acacia extract and its isolated compounds, methyl gallate and quercetin, mediated therapeutic angiogenesis in diabetic hind limb ischemia.